Analysis of the Claim Process Mechanism for Kafalah Financing Products in Mortgage Housing Liquidity Facilities (FLPP) at PT. Jamkrindo Sharia Medan Branch - Syahputri, Rima Rizki; Yafiz, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
KPR Sejahtera in the form of a Housing Financing Liquidity Facility or FLPP is one of the KPRs provided by banks. FLPP is a form of joint ownership of credit between public housing that has low interest rates and small monthly payments over the credit term. Here a third party is needed to provide guarantees for the security and protection of the house that has been credited, namely insurance, one of which is PT Jamkrindo Syariah. Kafalah Financing Prosperous Houses with Housing Finance Liquidity Facility (FLPP) is one of the products provided by PT. Guarantee Jamkrindo Syariah. The mechanism by which the Bank sends guarantee claims to Jamsyar is a matter that needs to be discussed. The purpose of this research is to find out how to submit a bank financing guarantee claim to Jamsyar. This research is a descriptive qualitative research using interview and documentation data collection methods. Sources of data received through literature studies and interviews. Based on the results of research at the Medan branch of PT Jamkrindo Syariah, the procedures that must be carried out by the Bank before submitting a claim are as follows: First, the bank conducts an analysis to determine whether the customer's financing is included in collectibility 4 or the category is doubtful. Second, the claim submission letter and supporting documents must be sent by the Bank to Jamsyar no later than 2 (two) months after the claim right is realized. Third, Jamsyar will review the claim submission file after receiving all the data or documents needed to submit a claim and ensure that all requirements are met, if the risk of loss of financing that occurs is included in the guaranteed risk, the guarantor must give approval and carry out claim payments.